A long-lasting taxonomic problem in European Sympycnus resolved, with the description of a new species and data on habitat preferences - Pollet, Marc; Persson, Magnus; Bøggild, Esben; Crossley, Roy (Zootaxa, 2015)
Type specimens of Sympycnus pulicarius, S. annulipes, S. cinerellus and S. desoutteri were examined to clear up a long-lasting taxonomic confusion. Our study revealed that they represent, together with S. pygmaeus and S. annulipes var. brunnitibialis, a single species, with S. pulicarius as the senior subjective synonym, which is redescribed in this paper. Lectotypes were designated for Dolichopus pulicarius, Porphyrops annulipes, Chrysotus cinerellus and Sympycnus desoutteri. The postpedicel in this species shows substantial variation in shape and size, but the presence of a posteroventral bristle on the mid tibia is more reliable and the particular chaetotaxy and relative lengths of the tarsomeres of the male hind tarsus are entirely consistent. Both latter features separate S. pulicarius from another species, S. septentrionalis sp. nov., that is described here. Ecological data on both species were examined. An analysis of Malaise trap and white pan trap samples collected in Belgium revealed that S. pulicarius is most common in the western part of Flanders, and most abundant in open grassy habitats. In contrast to S. pulicarius, which is widespread over Europe, S. septentrionalis sp. nov. seems confined to northern Europe, where it exhibits a similar habitat preference.